Decolonizing “Last Will Be First” and “Mission from the Margins”: A Missional Imperative - Jagessar, Michael N. (International review of mission, 2023)
AbstractThis contribution arose from the CWME's “decolonizing seminar” (5–9 June 2023), held in Lisbon on the theme “Making the last first.” Paying particular attention to mission archives and inherited missional-theological deposits, this essay makes a case for decolonizing mission as both habit and method to create systemic change. Decolonizing of mission as a process is for the whole of the oikos and ecumenical family and is not only a Western Europe and former colonies matter, as coloniality and empires transcend periods, events, and locations.